1995
DOI: 10.1046/j.1469-0705.1995.05030198.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of placenta accreta using transvaginal sonography and color Doppler imaging

Abstract: The safe use of transvaginal sonography in patients with placenta previa has been confirmed, and has revolutionized precise placental localization. The aim of our study was to evaluate the efficacy of transvaginal sonography and color-coded blood flow in the prediction of placenta accreta. Twenty-one patients with persistent placenta previa were scanned using transvaginal sonography and color-coded flow. Suspicion for placenta accreta consisted of total placenta previa at term with several placental lacunae ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(91 citation statements)
references
References 0 publications
4
86
0
1
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15] Other studies have indicated the utility of color Doppler sonography for the assessment of placenta accreta and the identification of vasa previa. 16,17 The current study shows that the administration of Levovist enhances the color Doppler signal of the placenta. Since it is not expected that Levovist, as an intact microbubble with a mean diameter of 2 to 3 µm, should cross the blood-placenta barrier, enhancement should be limited to the maternal circulation.…”
Section: Discussionmentioning
confidence: 54%
“…[5][6][7][8][9][10][11][12][13][14][15] Other studies have indicated the utility of color Doppler sonography for the assessment of placenta accreta and the identification of vasa previa. 16,17 The current study shows that the administration of Levovist enhances the color Doppler signal of the placenta. Since it is not expected that Levovist, as an intact microbubble with a mean diameter of 2 to 3 µm, should cross the blood-placenta barrier, enhancement should be limited to the maternal circulation.…”
Section: Discussionmentioning
confidence: 54%
“…9 The advent of Colour Doppler improved the diagnostic accuracy of conventionalgrayscalesonography. 5,7,8 The colour Doppler criteria suggestive of placenta accrete have been first described by Chou et al 8 They include:…”
Section: Discussionmentioning
confidence: 99%
“…The antenatal detection rate of placenta accreta (a collective term for accreta, increta and percreta) on ultrasound varies in the literature, ranging from 33% to 100%. 4,5 The Gray-scale sonography has been shown to be an excellent tool, with a sensitivity reported in the range of 77% to 87%, specificity of 96% to 98%, a positive predictive value (PPV) of 65% to 93%, and a negative predictive value (NPV) of 98%. 6 The use of colour Doppler and/ or power Doppler has been reported to improve the sensitivity and specificity of grey scale ultrasound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avanços recentes na US com dopler colorido e power Doppler permitiram o estudo dos vasos e a mensuração da velocidade e fl uxo do sangue placentário. Os padrões de pulsatilidade venosa associados à presença de lacunas venosas e ao fl uxo venoso complexo retroplacentário são considerados critérios doplerfl uxométricos para placenta acreta 2,11,12 . Achados na RM de acretismo placentário, como o hipersinal placentário invadindo o miomé-trio, foram primeiramente descritos em 1992 13 .…”
Section: Total 8 7 15unclassified